Upper Gastrointestinal Mucosal Injury and Symptoms in Elderly Low-Dose Aspirin Users - Yuji Shimada; Akihito Nagahara; Mariko Hojo; Daisuke Asaoka; Hitoshi Sasaki; Hiroya Ueyama; Kenshi Matsumoto; Sumio Watanabe (Gastroenterology Research and Practice)
Background. We investigated the prevalence, symptoms, and QOL impact of esophageal (EI), gastric (GI), and duodenal mucosal injury (DI) individually between low-dose aspirin (LDA) users and nonusers to reveal the clinical features of LDA-related mucosal injury. Methods. Data were extracted from the records of subjects who underwent upper gastrointestinal endoscopy at our department between April 2008 and December 2013. Responses from 3162 elderly patients on Frequency Scale for Symptoms of GERD (FSSG) and SF-8 QOL questionnaires (SF-8) were analyzed. FSSG items were classified into total score (TS), reflux score (RS), and dyspepsia score (DS). The SF-8 questionnaire consisted of the physical component summary (PCS) and mental component summary (MCS). Results. Prevalence among LDA users and nonusers, respectively, was 9.6% and 10.0% (P=0.83) for EI, 35.9% and 27.5% (P=0.0027) for GI, 3.3% and 3.4% (P=0.84) for DI, and 8.2% and 5.2% (P=0.036) for mucosal injury in 2 or more organs. LDA users diagnosed with EI had significantly lower PCS, LDA users diagnosed with GI had significantly lower DS, and LDA users diagnosed with DI had significantly lower RS and significantly lower MCS. Conclusion. These results provide important clinical information indicating that symptom-based management is not appropriate in LDA users regarding upper gastrointestinal mucosal injury.